2018
DOI: 10.1111/cge.13178
|View full text |Cite
|
Sign up to set email alerts
|

A critical appraisal of pharmacogenetic inference

Abstract: In essence, pharmacogenetic research is aimed at discovering variants of importance to gene-treatment interaction. However, epidemiological studies are rarely set up with this goal in mind. It is therefore of great importance that researchers clearly communicate which assumptions they have had to make, and which inherent limitations apply to the interpretation of their results. This review discusses considerations of, and the underlying assumptions for, utilizing different response phenotypes and study designs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 58 publications
0
8
0
1
Order By: Relevance
“…Similarly, prospective trials on genetically stratified groups are also mandatory to comparing treatment outcomes between different groups. 108,109 In other cases, clinical utility is determined by a "chain of indirect evidence" linking the results of a genetic test to intermediate data that are associated with improved clinical outcomes. 108,110 However, pharmacogenetic research remains an expanding field, and to date there is no unanimous consensus on the best appropriate study designs to uniquely evaluate drug-response variability related to genetic variations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, prospective trials on genetically stratified groups are also mandatory to comparing treatment outcomes between different groups. 108,109 In other cases, clinical utility is determined by a "chain of indirect evidence" linking the results of a genetic test to intermediate data that are associated with improved clinical outcomes. 108,110 However, pharmacogenetic research remains an expanding field, and to date there is no unanimous consensus on the best appropriate study designs to uniquely evaluate drug-response variability related to genetic variations.…”
Section: Discussionmentioning
confidence: 99%
“…108,110 However, pharmacogenetic research remains an expanding field, and to date there is no unanimous consensus on the best appropriate study designs to uniquely evaluate drug-response variability related to genetic variations. 109 Finally, several national drug agencies are carefully evaluating risk:benefit ratios in individual cases, carefully considering the concomitant pathologies (long QT syndrome, major arrhythmias, liver or kidney failure, electrolyte disorders), pharmacological associations (in particular for drugs that increase the QT), and above all the clinical anamnesis and identification with genetic diagnosis of favism (G6PD deficiency).…”
Section: Discussionmentioning
confidence: 99%
“…Increased CVD morbidity and mortality may be attributed to preexisting CVD in newly diagnosed cancer patients, cardiotoxicity resulting in decreased ventricular function, and treatment effects that result in increased CVRFs such as dyslipidemia, hypertension, central adiposity, and metabolic syndrome (Azard & Denmark-Wahnefried, 2014;Cespedes Feliciano et al, 2016;Coviello, Knobf, & Laclergue, 2013;Gristina et al, 2015;Simon et al, 2018). Genetic factors that produce variable susceptibility to both cancer treatment and toxicity may also be at play (Buzdar, Marcus, Blumenschein, & Smith, 1985;Patel, 2016;Smit, Noordam, le Cessie, Trompet, & Jukema, 2017).…”
Section: Cardiovascular and Cancer Riskmentioning
confidence: 99%
“…It has been observed that some patients develop toxicities to both chemotherapy and radiation at low doses while others can tolerate higher doses with no side effects (Buzdar et al, 1985;Patel, 2016;Smit et al, 2017). This variable susceptibility lends itself to the theory that there are genetic and clinical risk factors such as metabolic and inflammatory processes at play.…”
Section: Left Ventricular Dysfunction: Silent Dangermentioning
confidence: 99%
See 1 more Smart Citation